Assessing Time Predictability Features of ARM Big. LITTLE Multicores - Fernandez, Gabriel; Cazorla, Francisco J.; Abella, Jaume; Girbal, Sylvain (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
The increasing performance needs in critical realtime embedded systems (CRTES), such as for instance the automotive domain, push for the adoption of high-performance hardware from the consumer electronics domain. However, their time-predictability features are quite unexplored. The ARM big. LITTLE architecture is a good candidate for adoption in the CRTES market (i.e. in the automotive market it has already started being used). In this paper we study ARM big. LITTLE's capabilities to meet CRTES requirements. In particular, we perform a qualitative and quantitative assessment of its timing characteristics, focusing on shared multicore resources, and how this architecture can be reliably used in CRTES.